Discovery of Faint Nebulosity around a Z Camelopardalis–type Cataclysmic Variable in Antlia: Nova Shell or Ancient Planetary Nebula? - Howard E. Bond; Dana Patchick; Daniel Stern; Jonathan Talbot; John R. Thorstensen (The Astronomical Journal, 2025)
We report our discovery of a faint nebula surrounding a previously little-studied 15th mag variable star, ASASSN-19ds, in the Southern Hemisphere constellation Antlia. Spectra verify that the star is a cataclysmic variable (CV). Using new and archival photometry, we confirm that ASASSN-19ds is an eclipsing binary with an orbital period of 0.139 days (3.34 hr). Moreover, its out-of-eclipse brightness shows a “sawtooth” light curve with an amplitude of ∼1 mag and an interval between peaks that varies between about 3 to nearly 5 weeks. Its mean absolute magnitude in the Gaia system is M _G  = +6.5. These combined properties lead to a classification of ASASSN-19ds as a Z Camelopardalis–type CV. We obtained deep narrowband images of the nebulosity, using modest-sized telescopes and extremely long exposure times. Our imagery reveals a bipolar morphology, with thin arcs at the ends of the major axis, likely indicating an interaction with the interstellar medium. We consider several scenarios for the origin of the nebula, but from the existing information we are unable to distinguish between it being ejecta from an unobserved classical-nova outburst several centuries ago, or an ancient planetary nebula. Future observations should be able to decide between these possibilities. At the star’s distance of only ∼557 pc, a nova eruption would have been a spectacular naked-eye event.